Enhance performances of Co-free Li-rich cathode by eutesctic melting salt treatment. (February 2022) - Zhao, He; Li, Wenting; Li, Jinxing; Xu, Hanying; Zhang, Chao; Li, Jie; Han, Ce; Li, Zelin; Chu, Mo; Qiu, Xinping
Abstract: Lithium-rich layered oxides (LLOs) are one of the most promising cathodes for next-generation Li-ion batteries owing to their extraordinary energy density and low cost. However, the anionic redox reactions inevitably destabilize the oxygen framework and lead to oxygen release, which incurs voltage fading and capacity decay. Although less voltage fading can be realized in the cobalt-free iron-substituted materials, they still suffer from severe transition metal (TM) dissolution and poor kinetics. Herein, to ameliorate these drawbacks, we develop a novel eutectic melting salt treatment strategy. By controlling the melt and solidification of a LiF-MgF2 -CaF2 ternary salt, the robust fluoride coating layer and functional doping were synchronously conducted in a Co-free Fe-substituted Li-rich cathode Li1.2 Ni0.13 Fe0.13 Mn0.54 O2 . The outer fluoride layer effectively suppresses the oxygen release and prevents TM ion dissolution, while the inner doping elements improve the Li + diffusion kinetics and further stabilize the bulk crystal structure. Benefiting from these, the modified cathode exhibits significantly enhanced electrochemical performance, with negligible capacity loss from the 35th to the 120th cycles at 0.2 C, mitigated voltage fading, improved rate capability and better thermal stability as well. Graphical Abstract: ga1 Highlights: A LiF-MgF2 -CaF2 eutectic melting salt treatment strategy for Li-rich cathodes is reported for the first time. Coating and doping are synchronously realized in a Co-free Fe-substituted Li-rich cathode Li1.2 Ni0.13 Fe0.13 Mn0.54 O2 . Oxygen release is effectively mitigated to achieve the better electrochemical performance of Li1.2 Ni0.13 Fe0.13 Mn0.54 O2 cathode.